범불안장애의 불안증상에 대한 가미소요산의 제형별 효능 비교 임상연구의 중간보고 - 임정화; Jung Hwa Lim; 서복남; Bok Nam Seo; 이상룡; Sang Ryong Lee; 정인철; In Chul Jung (동의신경정신과학회지, 2010)
Objectives: The purpose of this research is to examine the efficacy of Gamisoyosan on anxiety of generalized anxiety disorder according to dosage form. Methods: In this randomized, double blinded, placebo-controlled study, we planned to give Gamisoyosan simple extract mixture or Gamisoyosan compound extract or controlled medication for major symptoms of generalized anxiety disorder. As preparatory research, Hamilton rating Scale for Anxiety(HAM-A) was measured as the 1st evaluative instrument, and Korean State-Trait Anxiety Inventory(STAI-K), Penn State Worry Questionnaire(PSWQ) Korean Beck`s Depression Inventory (BDI-K), Symptom Checklist-90-Revised(SCL-90R), WHO Quality of Life Abbreviated(WHOQOL-BREF) and Heart Rate Variability(HRV) were also measured as the 2nd evaluative instrument at the before treatment. Results: Demographic characteristics showed that there are Clinical characteristics-vital signs are within the normal range. The characteristics of disease-chief complaint, pattern Identification and etiological factor of the highest frequency number were worry, heart deficiency with timidity(心膽虛怯), family matters. The average period of disease in subjects is 6.31years. The results of Chest PA, EKG and clinicopathologic examination are within the reference range. The Scores of HAM-A, STAI-K, PSWQ were measured above the cutoff point. There are significant positive correlations among HAM-A, STAI-K, BDI-K and among HAM-A, STAI-K, PSWQ. There are no significant correlations between PSWQ and BDI-K. Conclusions: We considered that selection of subjects in this research is appropriately accomplished And this methodology is expected to be applied to the subsequent research. And also, we hope to make up for this study through various study and discussion.